System certyfikacji ''czysta turystyka'' podstawowe przesłanki decyzji wdrożeniowej - Dziuba, Radosław (Gospodarka w Praktyce i Teorii, 2012)
Poland, after a short recession resulting from the global crisis, again recorded growth in foreign tourist arrivals. This allows the conclusion that tourism will become in the coming years, one of the main directions of development Polish. In the wake of the development of tourism in Poland should take into account the need to increase the accommodation in hotels. This is necessary in order to fully exploit the potential of the country in this field. The hotels industry is so pro-development trend of tourism in Poland has a chance to growth. Beyond the basic offer, hotels need for additional distinguishing features compared to its nearest competitors such distinction through the use of certified sustainable solutions "Clean Tourism". The aim of this paper is to analyze the basic premises deployment decisions assumptions at the example of ecology certification "Clean Tourism" and an incentive to certify the hotel facilities.